EXPLORING THE EFFECTIVENESS VISUAL STIMULI TO IMPROVE WRITING SKILL OF EIGHT GRADERS - Serina; Febria, Desty; Marsevani, Maya (Universitas PGRI Palembang, 2025)
Writing is frequently regarded as the most challenging language skill for junior high school students to acquire. Many learners face difficulties in articulating their ideas in written form, often due to limited vocabulary, inadequate grammatical knowledge, and a lack of motivation. This Classroom Action Research was designed to enhance students’ writing proficiency through the integration of visual stimuli as an instructional technique. Conducted over two cycles with a cohort of 14 eighth-grade students at SMP Sultan Agung Batam, the study employed various instruments, including pre-tests, post-tests, classroom observations, and analysis of students’ written work. The findings revealed that visual stimuli significantly facilitated idea generation and led to improvements in both sentence construction and vocabulary usage. The students’ mean writing score rose from 52.86 in the pre-test to 67.64 in the post-test. These outcomes suggest that incorporating visual stimuli into writing instruction can serve as an effective pedagogical approach to strengthening students’ writing competence at the junior high school level.